2015
DOI: 10.1088/1748-9326/10/8/084016
|View full text |Cite
|
Sign up to set email alerts
|

Vertical ground motion and historical sea-level records in Dakar (Senegal)

Abstract: With growing concerns regarding future impacts of sea-level in major coastal cities, the most accurate information is required regarding local sea-level changes with respect to the coast. Besides global and regional sea-level changes, local coastal vertical ground motions can substantially contribute to local changes in sea-level. In some cases, such ground motions can also limit the usefulness of tide-gauge records, which are a unique source of information to evaluate global sea-level changes before the altim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The subsidence of the reclaimed land threatens infrastructure, and contributes to the relative sea level changes [62], which may cause saltwater intrusion [63,64] and destroy coastal biodiversity [37]. Assuming a mean sea level rise of 2.5 mm/year [33,65], the selected regions A, B, C, and D (shown in …”
Section: Effects Of Coastal Subsidence Coupled With Sea Level Changesmentioning
confidence: 99%
“…The subsidence of the reclaimed land threatens infrastructure, and contributes to the relative sea level changes [62], which may cause saltwater intrusion [63,64] and destroy coastal biodiversity [37]. Assuming a mean sea level rise of 2.5 mm/year [33,65], the selected regions A, B, C, and D (shown in …”
Section: Effects Of Coastal Subsidence Coupled With Sea Level Changesmentioning
confidence: 99%
“…Previous studies have reported on vulnerable sites for coastal subsidence and short-term sea level rise, including Hampton Roads, Virginia [14], New York City [15], Taiwan [16], and North Carolina [17]. Hence, the estimation and correction of the local ground motion at and around the tide gauges is important to minimize uncertainties in the local and global sea level changes observed [18][19][20][21][22][23]. In recent decades, long-term glacial adjustments were quantified using historical variations and climate models for the reconstruction of sea level records [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…They show that the combined GNSS and InSAR products yield deeper physical understanding and predictive power for beach morphology evolution. Subsequent studies have explored various methods based on InSAR measurements to further assess its applicability in different coastal environments Wöppelmann et al, 2013;Le Cozannet et al, 2015), confirming its usefulness in sea level studies. InSAR, being more reliable in urban (or arid) areas than in vegetated areas, is particularly efficient for measuring surface displacements in coastal megacities.…”
Section: Vertical Land Motionsmentioning
confidence: 85%